TENDENCIES OF DEVELOPMENT IN THE FIELD OF FINANCIAL OUTSOURCING IN RUSSIA AND ABROAD - S. E. Zolotareva (Модернизация, инновация, развитие, 2018)
Purpose: the purpose of this article is to determine the prospects for the development of financial outsourcing in the sphere of accounting, taxation and management (corporate) accounting as a type of entrepreneurship in Russia. To achieve this purpose, it is necessary to solve the following tasks: to analyze the theory and practice of the current state of financial outsourcing and its growth in Russia and abroad; to identify the prospects for its development in Russia.Methods: the research was conducted by using systematic, logical, comparative analysis, grouping and generalization methods, which made it possible to ensure the validity of the results and conclusions of the research.Results: prospects for the development of financial outsourcing are expressed in the introduction of modern information technologies into the outsourcing practice, which contribute to the expansion of the target segment due to a significant reduction of outsourcing services prices. Trends in the development of financial outsourcing are also associated with the transition of society to the digital economy model and manifested in the further automation and robotization of routine functions with the prospect of integrating all business transactions into a single database, both on a national and global scale.Conclusions and Relevance: the implementation of technologies that reduce the cost of services should become an important part of outsourcing development strategy in the short term, as it will expand the range of users of financial outsourcing, which can become a "point of growth" both in terms of revenues and profits from new ones and in terms of profits from existing customers. The companies that first implement such technologies will get a serious competitive advantage and will be the first who will attract a larger business to outsourcing.